Species identification of introduced veronicellid slugs in Japan - Hirano,Takahiro; Kagawa,Osamu; Fujimoto,Masanori; Saito,Takumi; Uchida,Shota; Yamazaki,Daishi; Ito,Shun; Mohammad Shariar,Shovon; Sawahata,Takuo; Chiba,Satoshi (PeerJ, 2022)
Reliable identification of species is important for protecting native ecosystems against the invasion of non-native species. DNA barcoding using molecular markers, such as the mitochondrial cytochrome oxidase subunit 1 (COI) gene, helps researchers distinguish species. In this study, we focused on introduced veronicellid slugs in the Ryukyu Islands and some greenhouses on mainland Japan. Some veronicellids are medium-to-high risk pest species for humans. Identifying veronicellid species by their external morphology is difficult and unreliable because there is substantial overlap between intraspecific variation and interspecific differentiation. Therefore, internal morphologies such as male genitalia have been the primary traits used to distinguish veronicellids. To identify introduced veronicellid slugs in Japan to the species level, we used morphological assessment of male genitalia and DNA barcoding of the standard COI gene fragment. We also conducted species-delimitation analyses based on the genetic data. The results showed that five evolutionarily significant units, corresponding to four nominal species inhabit the Ryukyu Islands, of which two species were also found in the greenhouses of mainland Japan, including the first record of Sarasinula plebeia in Japan. The presence of non-native slug species could increase the transmission of parasites in Japan.
Keywords: COI; Mollusks; Veronicellidae; Sarasinula plebeia; Semperula wallacei; Laevicaulis alte; Greenhouses; Ryukyu Islands